2020
DOI: 10.3390/antiox9080676
|View full text |Cite
|
Sign up to set email alerts
|

SkQ1 Suppresses the p38 MAPK Signaling Pathway Involved in Alzheimer’s Disease-Like Pathology in OXYS Rats

Abstract: Alzheimer’s disease (AD) is the most common type of dementia and is currently incurable, and mitogen-activated protein kinase (MAPK) p38 is implicated in the pathogenesis of AD. p38 MAPK inhibition is considered a promising strategy against AD, but there are no safe inhibitors capable of penetrating the blood–brain barrier. Earlier, we have shown that mitochondria-targeted antioxidant plastoquinonyl-decyltriphenylphosphonium (SkQ1) at nanomolar concentrations can prevent, slow down, or partially alleviate AD-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Here, we showed for the first time that the progression of AD-like pathology in OXYS rats takes place simultaneously with alterations in the expression of nine genes encoding proteins participating in the ERK1/2 SP, whereas dietary supplementation with SkQ1 normalizes the expression of eight of these genes. In our previous studies, we have demonstrated that after supplementation with SkQ1 in OXYS rats, the expression of 14 genes involved in MAPK signaling cascades changes [20], of which 12 are affiliated with the p38 MAPK SP [21]. In the present study, we found that products of the remaining two genes take part in the ERK1/2 SP.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Here, we showed for the first time that the progression of AD-like pathology in OXYS rats takes place simultaneously with alterations in the expression of nine genes encoding proteins participating in the ERK1/2 SP, whereas dietary supplementation with SkQ1 normalizes the expression of eight of these genes. In our previous studies, we have demonstrated that after supplementation with SkQ1 in OXYS rats, the expression of 14 genes involved in MAPK signaling cascades changes [20], of which 12 are affiliated with the p38 MAPK SP [21]. In the present study, we found that products of the remaining two genes take part in the ERK1/2 SP.…”
Section: Discussionsupporting
confidence: 63%
“…Using nontransgenic senescence-accelerated OXYS rats, which develop neurodegenerative changes that are similar to the signs of the sporadic type (>90% of cases) of AD in humans [19], we have previously reported that treatment with SkQ1 between ages 12 and 18 months-that is, during active progression of AD-like pathology in these animals-alleviates structural neurodegenerative alterations, improves the structural and functional state of mitochondria, prevents the neuronal loss and synaptic damage, enhances a neurotrophic supply, and decreases Aβ 1-42 peptide levels and tau hyperphosphorylation in the hippocampus, thus resulting in improvements in learning ability and memory [15][16][17]. Via transcriptomic approaches, we then found that the anti-AD properties of SkQ1 are related to improvements in the activities of many intracellular processes and SPs in the prefrontal cortex and hippocampus, including the p38 MAPK SP [20,21], which is launched during the development of AD-like pathology in OXYS rats [22]. In this study, we continued to investigate the mechanisms of the anti-AD effects of SkQ1 in OXYS rats at an advanced stage of AD-like pathology and focused on MEK1/2-ERK pathway alterations in the hippocampus.…”
Section: Introductionmentioning
confidence: 86%
“…Other p38 MAPK inhibitors have been reported to have beneficial effects in cell culture and rodent models of AD but the selectivity of these inhibitors for p38 MAPK has not been well-documented [ 327 , 328 , 329 , 330 , 331 ]. Some studies have used p38 MAPK inhibitors that are selective, but their ability to suppress neuropathology or improve behavioral performance in vivo was not been adequately evaluated [ 332 ].…”
Section: The Enzymesmentioning
confidence: 99%
“…In addition, SkQ1 decreased A β 40, A β 42, total and p-Tau, and improved learning and memory in these rats. Mitochondrial function has not been assessed in SkQ1-treated OXYS rats 292 , 293 , 294 , 295 . A ubiquinone compound, MitoQ, which targets the mitochondria due to a covalently bound lipophilic cation triphenylphosphonium, has been shown in 3xTg-AD mice to increase learning and memory and synaptophysin level and decrease GFAP, IBA1, and A β 42, total and p-TAU 296 , 297 .…”
Section: Targeting Mitochondrial Bioenergetics and Mitochondrial Qual...mentioning
confidence: 99%